Post-Traumatic Stress Reactions in Caregivers of Children and Adolescents/Young Adults with Severe Diseases: A Systematic Review of Risk and Protective Factors - Carmassi, Claudia (Int J Environ Res Public Health, 2020)
Severe illnesses in children and adolescents/young adults (AYAs) may represent a complex burden for patients and their caregivers, including a wide range of mental disorders, particularly post-traumatic stress disorder (PTSD). Few events are as potentially traumatizing as having a son or a daughter diagnosed with a severe, life-threatening, or disabling disease. The presence of PTSD symptoms in caregivers may compromise their efficacy as caregivers and negatively affect the child’s well-being. This systematic review aims at outlining potential risk and protective factors for the development of PTSD symptoms in caregivers of children and AYAs affected by severe acute or chronic illnesses. Thirty-one studies on caregivers of children and AYAs affected by severe, acute, or chronic diseases were included. Socio-demographic and socio-economic characteristics, illness-related distress, psychiatric symptoms, support, and coping styles were found as potential risk/protective factors across studies. It is crucial to consider risk factors affecting caregivers of severely ill young patients, in order to plan focused interventions aimed at preventing an adverse clinical outcome in caregivers and at enhancing caregivers’ coping skills, in order to ultimately improve their quality of life.